RHODODENDRON WIDJAJAE (ERICACEAE, SECTION SCHISTANTHE) A NEW SPECIES FROM SULAWESI - Argent, George; Mambrasar, Yasper Michael (REINWARDTIA, 2019)
ARGENT, G. & MAMBRASAR, Y. M. 2019.  Rhododendron widjajae (Ericaceae, section Schistanthe) a new species from Sulawesi. Reinwardtia 18(1): 27‒30. — A new species of Rhododendron section Schistanthe (= subgenus Vireya) is described, Rhododendron widjajae Argent & Mambrasar. It is compared with the two most similar species and the differences demonstrated.